Evaluation of Photobiogoverning Role of Blue Light Irradiation on Viral Replication. (24th September 2021) - Oh, Phil‐Sun; Kang, Kyung Won; Ryu, Seung Rok; Lim, SeokTae; Sohn, Myung‐Hee; Lee, Sang‐Myeong; Jeong, Hwan‐Jeong
Abstract: Most recently, severe acute respiratory syndrome coronavirus‐2 has triggered a global pandemic without successful therapeutics. The goal of the present study was to define the antiviral effect and therapeutic action of blue light irradiation in SARS‐CoV‐2‐infected cells. Vero cells were infected with SARS‐CoV‐2 (NCCP43326) or mock inoculum at 50 pfu/well. After blue light irradiation, the inhibitory effect was assessed by qPCR and plaque reduction assay. When Vero cells were irradiated to blue light ranging from 1.6 to 10 J cm −2, SARS‐CoV‐2 replication was inhibited by up to 80%. The antiviral effect of blue light irradiation was associated with translation suppression via the phosphorylation of eIF2α by prolonging endoplasmic reticulum (ER) stress. The levels of LC3A/B and Beclin‐1, which are key markers of autophagy, and the levels of PERK and PDI for ER stress were highly increased, whereas caspase‐3 cleavage was inhibited after blue light irradiation in the later stage of infection. Our data revealed that blue light irradiation exerted antiviral and photo‐biogoverning activities by prolonging ER stress and stimulating autophagy progression during viral infection. The findings increase our understanding of how photo‐energy acts on viral progression and have implications for use in therapeutic strategies against COVID‐19. Abstract : SARS‐CoV‐2 is a single stranded RNA virus with crown‐like spike (S) glycoproteins that uses it to mediate viral attachment, fusion, and entry, subsequently infect host cells. Irradiation with blue light after SARS‐CoV‐2 infection promoted ER stress protein expression as well as eIF2α phosphorylation even 48 h post‐infection. This prolonged ER stress by blue light irradiation could block translation initiation and shutdown cellular protein synthesis, resulting in the inhibition of viral replication. One possibility is that ROS production caused by blue light irradiation could assist as a signaling molecule that directly/or indirectly stimulates ER stress and the autophagic process.